CDS channels of influence on discretionary accruals - CHENG, Hao (Institutional Knowledge at Singapore Management University, 2022)
Existing studies indicated that firm debt holders can use the credit default swap (CDS) market to hedge their credit risk, and thus they would reduce their monitoring of the firms, leading to largely distressed firms shirking and increasing positive abnormal earnings accruals. Besides providing insurance, however, the CDS spreads also perform price discovery of credit risk information sought by trade creditors and potential lenders who are not protected. High absolute abnormal discretionary accruals or bad earnings quality, especially negative abnormal accruals, would lead adverse CDS price signals that are very costly to the firm. This compels the firm under nondistressed conditions to be able to improve cash holdings, cash flows, working capital, and earnings reporting quality. Our new results indicate that the channels of improvement in earnings quality are through a firm's large accounts payable and low cash holdings related to trade credit exposures. In the longer run, this leads to higher profitability and improved firm value. Thus, the generation of public information via the CDS market reduces information asymmetry and can enforce greater discipline in discretionary accounts reporting.